Omset Penjualan, Persepsi Pelaku UMKM dan Pemahaman Akuntansi terhadap Implementasi SAK EMKM - Maria Febi Sekar Utami; Theresia Dwi Astuti (Journal of Management and Bussines (JOMB), 2024)
This research aims to determine the influence of Sales Turnover, Perceptions of MSME Players and Understanding of Accounting on the Implementation of SAK EMKM. The research method used for sampling in this study used random sampling. The research results show that the R Square (R2) value is 0.366, meaning that 36.6% of the variation in the application of SAK EMKM is explained by accounting understanding, perceptions of MSME actors, and company turnover. Conclusions, based on showing that sales turnover, perception of SMEs, and understanding of accounting have a significant positive effect on SME implementation. Keywords: Sales Turnover, Perception, Understanding, SAK EMKM